Новий метод відновлення зображень в зонах відсутності попіксельної інформації - Литвин, О.М.; Литвин, О.О.; Лісний, Г.Д.; Славік, О.В. (Управляющие системы и машины, 2017)
Задача відновлення зображення в зонах відсутності попіксельної інформації є вкрай актуальною. Такі задачі виникають в машинобудуванні, сейсмографії, обробці даних дистанційного зондування Землі. Для розв’язання такого роду задач розроблено метод інтерстрипації, в даній статті взятий за основу для нового модифікованого методу. Задача восстановления изображения в зонах отсутствия попиксельной информации крайне актуальна. Такие задачи возникают в машиностроении, сейсмографии, обработке данных дистанционного зондирования Земли. Для решения такого рода задач разработан метод интерстрипации, в данной статье взятый за основу для нового модифицированного метода. Sometimes in the files containing the graphics information defects (empty subareas of image, etc.) are detected. So, it is urgent to develop the methods for image reconstruction in those parts, where the information is missing, or it is not fully known (for example, damaged). The task of restoring the image in the areas of absence of information about pixels is extremely important. Such problems arise in engineering, seismography, processing of remote sensing data, etc. To solve such problems Lytvyn O.N. and Matveeva S.Y. has developed the method of interstripation, that are received from satellites or from radar installed on airplanes. In given work this method has been used as a basis to create a modified method of interstripation. In this article the theoretical foundations of modified method of interstripation and the standard method of interstripation are presented. The computational experiments are carried out for the cases where the unidentified area are presented as a system of horizontal, vertical or orthogonally related stripes. In all cases the images are restored by the modified method of interstripation and the standard method of interstripation. The obtained results are compared between themselves and with the original image.